PERUBAHAN BIROKRASI PEMERINTAHAN DAERAH KEWEDANAAN RAWAS 1943-1950: Sejarah - Supian Ramli; Lagut Bakaruddin (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2020)
During the Japanese government, the bureaucracy during the Dutch East Indies government was still carried out, but only the name changed. Rawas, which is an Ondeer Afdeelig area, has changed its status to Gun Rawas, but in the near future the Japanese government will form a district level area, namely Musi Ulu Rawas. This study uses a historical method which consists of several stages such as Heuristics, Criticism, Interpretation and Historiography. The results of this study can describe the changes in the local government system of Rawas and eventually it became Musi Ulu Rawas Regency in its development into Musi Rawas Regency.